Universiti Tun Hussein Onn Malaysia (UTHM) / Muhammad Azriaiman Eisam - Eisam, Muhammad Azriaiman (Faculty of Business and Management, 2023)
I made the made the decision to complete my training at the Industrial and Community Relations Centre (ICRC) at Tun Hussein Onn University (UTHM). In Batu Pahat, there is a public university called UTHM. With that said, I go into detail in my report about my six months of industrial training, including a thorough introduction to the organization's goals, structure, mission, and vision, as well as the inclusion of UTHM in those. On the other hand, I also provide my most recent resume and the knowledge I picked up from my internship in other sections of this report. I shall list both internal and external benefits I obtained from this company throughout my internship in this report and paper. My goal is to discuss the knowledge and experience I gained while training. In this industry training report, I analyze the SWOT analysis of the organization, which consists of their strengths, weaknesses, opportunities, and threats. In this research, I also provide some recommendations for organizations on how to deal with their dangers and weaknesses while using their chances and strengths.